Foreign agents or agents of justice? Private foundations, backlash against non‐governmental organizations, and international human rights litigation. Issue 1 (14th March 2023) - Haddad, Heidi Nichols; Sundstrom, Lisa McIntosh
Abstract: The premise of Russia's 2012 "Foreign Agents" Law, one of the first such laws restricting foreign funding for non‐governmental organizations (NGOs), is that foreign monies equal foreign agendas. Since then, over 50 countries have adopted similar laws using a similar justification. This paper interrogates this claim of foreign donor influence through examining legal mobilization by human rights NGOs at the European Court of Human Rights (ECtHR). We track donor support for litigation by providing an overview of all foundation grant flows relating to strategic litigation for 2013–2014, and then matching the granting activities of two major U.S. foundations over 14 years to human rights NGO participation in cases before the ECtHR. Further, through case studies of Russian NGOs, we assess the causal role that donor support has played in facilitating their increased involvement in ECtHR litigation. The combined analysis indicates broad patterns of private foundation support to litigating NGOs, but uncovers no evidence that foreign donors were "pushing" NGOs toward litigation as a strategy, but instead more evidence suggesting that NGOs convinced donors to support human rights litigation. Despite the inaccuracy of the justification underpinning Russia's foreign agent law, the law threatens the survival of human rights organizations.